A comparative, cross-over, double blind, randomized study for bioequivalence assessment between two formulations of valsartan capsules vs. tablets. (Colombia Medica, 2006)
Introduction: Bioequivalence or compared equivalence studies are used to demonstrate claims that the new product, named generic product, will have the same bioavailability as the reference product, named brand product. If two products are bioequivalent it means that they would expect to have the same efficacy and security. Bioequivalence is established by the statistical estimation of significant differences or not in the pharmacokinetics parameters of area under the curve (AUC) and maximum concentration (Cmax). In this case, bioequivalence will be evaluated and the bioavailability of valsartan will be compared. Valsartan is an agent antihypertensive and specific angiotensin II antagonist acting on the AT1 receptor subtype. Objective: The aim of this study was to evaluate the bioequivalence of two pharmaceutical products whose active principle is Valsartan, based on the comparison of the pharmacokinetic measures of rate and extent (in terms of required time) in which valsartan reaches the sanguineous circulation after a oral dose to 15 volunteers. Metodology: This was a randomized crossover double blind single-dose study on 15 male healthy volunteers aged between 19 and 28 years. The study was performed in two periods. Each treatment period consisted of a single-dose of 320 mg valsartan, with a wash-out time of 8 days between the first and second period. Plasma concentrations of valsartan were evaluated by HPLC/UV with method of addition of valsartan standard and losartan as internal standard. Results: Valsartan tablets formulation showed this pharmacokinetic parameters: AUC 44,893 µg/mlxh, Cmax 6,430.3 µg/ml and Tmax 2 h. Valsartan capsules formulation showed this pharmacokinetic parameters: AUC 44,963 µg/mlxh, Cmax 5,831.4 µg/ml and Tmax 2.5 h. Conclusion: The study showed no statistically significant differences in the plasma concentration levels after administration of the two formulations of valsartan: 80 mg tablets and 80 mg capsules. So, the design of the study and the application of the protocols chosen enabled the demonstration of bioequivalence between the products.